Partially repeatable genetic basis of benthic adaptation in threespine sticklebacks. (1st April 2016) - Erickson, Priscilla A.; Glazer, Andrew M.; Killingbeck, Emily E.; Agoglia, Rachel M.; Baek, Jiyeon; Carsanaro, Sara M.; Lee, Anthony M.; Cleves, Phillip A.; Schluter, Dolph; Miller, Craig T.
Abstract: The extent to which convergent adaptation to similar ecological niches occurs by a predictable genetic basis remains a fundamental question in biology. Threespine stickleback fish have undergone an adaptive radiation in which ancestral oceanic populations repeatedly colonized and adapted to freshwater habitats. In multiple lakes in British Columbia, two different freshwater ecotypes have evolved: a deep‐bodied benthic form adapted to forage near the lake substrate, and a narrow‐bodied limnetic form adapted to forage in open water. Here, we use genome‐wide linkage mapping in marine × benthic F2 genetic crosses to test the extent of shared genomic regions underlying benthic adaptation in three benthic populations. We identify at least 100 Quantitative Trait Loci (QTL) harboring genes influencing skeletal morphology. The majority of QTL (57%) are unique to one cross. However, four genomic regions affecting eight craniofacial and armor phenotypes are found in all three benthic populations. We find that QTL are clustered in the genome and overlapping QTL regions are enriched for genomic signatures of natural selection. These findings suggest that benthic adaptation has occurred via both parallel and nonparallel genetic changes.